Balanced Scorecard Performance of Business Study Program of Telkom University Surabaya - Aulia, Darlin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The study examines the advancements made by Telkom University Surabaya in lecturer development, certification, and continuous education, which align with the institution's goals and contribute to high customer satisfaction as indicated by EDOM scores. The growth of the Digital Business program is highlighted through increased enrollment and the acquisition of external scholarships from Kedaireka and BIMA. Future strategies are outlined, focusing on enhancing financial independence, service quality, and strengthening partnerships with industry and government, all while aiming to improve faculty and program reputation. These initiatives are integral to supporting Vision 2025 objectives, emphasizing the advancement of research, collaboration with small and medium-sized enterprises (SMEs), and community service, thus driving comprehensive institutional progress.